Energy transfer in co-doped NaI:(Tl,Eu) crystals - Gridin, S.; Vasyukov, S.; Shiran, N.; Gektin, A. (Functional Materials, 2014)
The energy transfer mechanism in Eu doped and Tl, Eu co-doped NaI crystals is discussed. The self-trapped exciton emission band overlaps stronger with Eu²⁺ excitation bands rather that with Tl⁺. This suggests that transfer STE -> Activator can be more efficient in Eu²⁺ co-doped NaI:Tl crystals. Theoretical estimation of energy transfer efficiency was done based on the Forster model. It is shown that Europium concentration of 1 mass% or above is required for efficient dipole-dipole energy transfer. However, this concentration is not reachable in NaI:(Tl,Eu) due to the solubility limit of Eu²⁺ in NaI crystal.